2009
DOI: 10.2174/187220809788700201
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Tissue Models for Drug Discovery and Toxicology

Abstract: Launching a new drug on the market is an extremely time-consuming and expensive process. The total costs from the lab bench to the patient's bedside are in the range of $800 million for each new compound. Innovative pre-clinical assays are urgently needed to select the most promising drug candidates. High-throughput molecular screening does not provide information on the effects on cellular functions. Testing on animals is expensive, ethically controversial, and poorly predictive of the response in humans. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 39 publications
0
58
0
Order By: Relevance
“…Hence, this has led to the development of a number of 3D in vitro 66 intestinal models. It is suggested that these 3D models could be useful to investigate 67 tissue engineering, drug discovery, and used as an alternative to in vivo animal 68 models in drug toxicity studies [3][4][5]. Previously, in vitro intestinal models have been 69 limited to 2D cell culture [6,7], however, a number of studies have attempted to [2,8,9].…”
mentioning
confidence: 99%
“…Hence, this has led to the development of a number of 3D in vitro 66 intestinal models. It is suggested that these 3D models could be useful to investigate 67 tissue engineering, drug discovery, and used as an alternative to in vivo animal 68 models in drug toxicity studies [3][4][5]. Previously, in vitro intestinal models have been 69 limited to 2D cell culture [6,7], however, a number of studies have attempted to [2,8,9].…”
mentioning
confidence: 99%
“…It is currently acknowledged that establishing 3D cell-cell interactions and using ECMs or 3D gels reduces the gap between cell culture and real tissue. There are strong indications that toxicity assays based on 3D cultures of human cells provide more accurate results than two-dimensional cultures (Pampaloni et al 2009). Three-dimensional cultures are promising for toxicity screening of chemicals and to sort out toxic substances at early stages of drug discovery.…”
Section: Spim Applicationsmentioning
confidence: 99%
“…Three-dimensional tissue engineering and microtechnology fabrication will narrow the gap between in vitro and in vivo systems (63,77,105). Cells in tissues receive signals from diverse cellular partners; certain pathways may be activated only when these multiple cell types are present (63,76,77).…”
Section: Stem Cellsmentioning
confidence: 99%
“…Cells in tissues receive signals from diverse cellular partners; certain pathways may be activated only when these multiple cell types are present (63,76,77). Stem cells, with their ability to reproducibly form tissue-like 3-D structures in heterogeneous cultures, are likely to produce assay systems that better emulate in vivo conditions (18).…”
Section: Stem Cellsmentioning
confidence: 99%